Non-Alcoholic Fatty Liver Disease: Current Perspectives and Future Direction in Disease pathogenesis, Treatment and Diagnosis - Athinarayanan, Shaminie (2012)
Non-alcoholic fatty liver disease (NAFLD) is one of the most common liver diseases in the world. An important implication of this disease is the progression of the disease to a more complicated condition called non-alcoholic steatohepatitis (NASH) and the wide variety of clinical presentations. Over the past 5 years, remarkable progresses have been made in understanding the genetic basis for the disease. Recent clinical trials in pharmacotherapy for the disease have been encouraging as well. It is anticipated that the integration of the wide spectrum information retrieved from genomics, transcriptomics and proteomics studies conducted in NAFLD and NASH will mediate a better understanding of the disease pathogenesis and facilitate the postulation of disease pathobiology pathways. Genetic and biological markers identified from the omics studies may hold promise for diagnosis, personalized treatment, early prevention and new drug development.